Health Literacy Status and Its Related Factors in the Elderlies in Dorood, Iran - Sahar Sabooteh; Hossein Shahnazi; Firoozeh Mostafavi (Journal of Education and Community Health)
Aims: Elderly people with low levels of health literacy, as one of the most at-risk groups, have some problems regarding the perception of information related to their health. This study was conducted with the aim of determining health literacy status in elderly population of Dorood, Iran. Materials and Methods: This cross sectional descriptive-analytical study was conducted on 220 elderly people referring to health centers in Dorood in 2017. The sampling method was first stratified random sampling. To collect information, the Test of Functional Health Literacy in Adults (TOFHLA) was used as self-report. Data were analyzed by SPSS 20 software, using Pearson correlation coefficient, Spearman correlation, independent t-test, and one-way ANOVA. Findings: The mean age of participants in this study was 66.29 ± 7.57 years. The results of this study showed that the mean of health literacy score in the subjects was56.45± 19.9 from 100 and the health literacy of 57.2% of the elderly was insufficient. This study showed that there is a significant relationship between health literacy with age, education level and income (p <0.05). Conclusion: The health literacy of elderlies is low in Dorood and the level of inadequate health literacy is less common in people with older ages, lower education, and lower income levels.